Evaluating the suitability of fyke nets for small-scale fisheries in the Free State Province of South Africa - LM Barkhuizen; OLF Weyl (Water SA, 2020)
South Africa is under increasing pressure to develop small-scale fisheries in inland waters. To inform appropriate development of this sector in the Free State Province, the catch rate of double-ended fyke nets was evaluated using survey data from 20 impoundments sampled during the 2013/2014 summer season. Fyke nets were set over night and the total sample effort was 114 fyke net nights. Overall catch per unit effort (CPUE) was 16.8 ± 28.3 kg·net-1·night-1 and catch composition was dependent on impoundment, but generally comprised of a mixture of common carp Cyprinus carpio, African sharptooth catfish Clarias gariepinus, smallmouth yellowfish Labeobarbus aeneus, Orange River mudfish Labeo capensis and moggel Labeo umbratus. The influence of temperature and the potential benefits of baiting the nets were subsequently evaluated through monthly sampling in the hyper-eutrophic Krugersdrift Dam and at the oligotrophic Gariep Dam. Baiting did not significantly influence CPUE, which was significantly higher at Krugersdrift Dam (19.97 ± 23.22 kg·net-1·night-1) than at Gariep Dam (5.02 ± 6.05 kg·net-1·night-1). Increasing temperature had a positive effect on CPUE at Krugersdrift Dam but not at Gariep Dam. Species composition also differed between impoundments and, as a result, we conclude that seasonal catch rates and species compositions will need to be evaluated prior to implementation of fyke net fisheries in specific localities.